Lashing Out after Stewing over Public Insults: The Effects of Public Provocation, Provocation Intensity, and Rumination on Triggered Displaced Aggression. Issue 1 (5th October 2012) - Vasquez, Eduardo A.; Pedersen, William C.; Bushman, Brad J.; Kelley, Nicholas J.; Demeestere, Philippine; Miller, Norman
<x xml:space="preserve">Abstract</x> Four studies present the first evidence showing that public (vs. private) provocation augments triggered displaced aggression by increasing the perceived intensity of the provocation. This effect is shown to be independent of face‐saving motivation. Following a public or private provocation, Study 1 participants were induced to ruminate or were distracted for 20 min. They then had an opportunity to aggress against another person who either acted in a neutral or mildly annoying fashion (viz. triggering event). As expected, the magnitude of the greater displaced aggression of those who ruminated before the triggering event compared with those distracted was greater under public than private provocation. Study 2 replicated the findings of Study 1 and confirmed that public provocations are experienced as more intense. Studies 3 and 4 both manipulated provocation intensity directly to show that it mediated the moderating effect of public/private provocation found in Study 1. The greater intensity of a public provocation increases reactivity to a subsequent trigger, which in turn, augments triggered displaced aggression. Aggr. Behav. 39:13‐29, 2013. © 2012 Wiley Periodicals, Inc.